"Unconstitutional Constitutional Amendments?": Exploring The 1973 Sabah Constitutional Amendment That Declared Islam The State Religion - Mohd. Nazim Ganti Shaari (Kajian Malaysia, 2014)
When North Borneo agreed to join Malaya, Singapore and Sarawak to form the Federation of Malaysia, among the guarantees that it requested was that Islam not be designated the state religion of Sabah. The request arose out of various missions carried out to ascertain the wishes of the Sabahans. However, in 1973, the State Constitution of Sabah was amended to insert Article 5, which declared Islam to be Sabah's state religion. Although this exercise of the "popular sovereignty of the people" might not be out of place in the context of "representing the popular will of the people", this particular constitutional amendment is peculiar when examined in light of various historical constitutional documents related to North Borneo because the amendment suggests that historical antecedents are not relevant in shaping a constitution. A constitution cannot be divorced from the history of its people but at the same time, putting a large premium on history would result in an outdated constitution: it has often been said that a constitution must be flexible to accommodate the wishes of the present generation of citizens. Accordingly, the validity of Article 5 must be scrutinised from all angles to determine whether its assumption of "representing the popular will of the people" is valid. This process ensures that constitutional change is not solely subject to the whims of the legislative body, which might be dictated by political concerns and personal ambitions due to the nature of politics and the political process.